(3CSGSjGJ GdeMGSHI aj GdTQcGJ GdeSGgeIs - (3CMeO Mdej(B, (3LeYIs; (3eDjO QGVj NfaQ(B, s ((3YeGf(B:s (3OGQ UaGA ddfTQ hGdJhRjY,s, 1998)
(3WHjYI GdTQcGJ GdeSGgeI, GdeYGdLI GdeMGSHjI dQCS GdeGd aj GdTQcGJ GdeSGgeI, GdeYGdLI GdeMGSHjI dESfGO GdbQhV aj GdTQcGJ GdeSGgeI, GdJbGQjQ GdeGdjI hJhRjY GdCQHGM aj GdTQcGJ GdeSGgeI, GdeYGdLI GdeMGSHjI dJMhd hEfOeGL GdTQcGJ GdeSGgeI, GdeYGdLI GdeMGSHjI dJUajI GdTQcGJ GdeSGgeIs
(3HHdjhZQGajG(B: (3U(B.239s
Keywords: (3GdTQcGJ GdeSGgeIs; (3GdeMGSHIs